PENGARUH MARKETING CAPABILITY TERHADAP FINANCIAL PERFORMANCE DENGAN INNOVATION CAPABILITY SEBAGAI VARIABEL INTERVENING PADA INDUSTRI PERHOTELAN DI SURABAYA - Yong, Liem Boen (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of marketing capability to innovation capability; innovation capability to financial performance; and marketing capability to financial performance in hospitality industries in Surabaya. This study used a quantitative approach, and the data were obtained by distributing questionnaires to hospitalities industries in Surabaya and then processed by using smartPLS software. This study showed that there was positive and significant relationship of marketing capability to innovation capability; innovation capability to financial performance; and marketing capability to financial performance in hospitality industries in Surabaya. Innovation capability was adequate to become an intervening variable between marketing capability and financial performance gave greater affect than direct relationship between marketing capability and financial performance.